Vertrauen und chinesisches Wirtschaftshandeln in Singapur: Zur kulturellen und sozialstrukturellen Bedingtheit von Vertrauensbildung und Kooperation in chinesischen Geschäftsbeziehungen - MENKHOFF, Thomas (Institutional Knowledge at Singapore Management University, 1995)
Based on in-depth interviews with Chinese merchant exporters in Singapore, the article explores why personal forms of trust (the Chinese translation is xinyong) are key elements in the complex web of business and associated social relationships.